Radiographic predictors of symptomatic locking screw removal after treatment of tibial fractures with intramedullary nails. Issue 12 (December 2018) - Mascarenhas, Daniel; Connelly, Daniel; O'Hara, Nathan N.; Gage, Mark J.; Coale, Max; Manson, Theodore T.; O'Toole, Robert V.
Abstract: Introduction: The purpose of this study was to determine the radiographic parameters associated with symptomatic locking screw removal after intramedullary tibial nail insertion. Our hypothesis was that locking screws located closer to joints and those extending longer than the width of the bone result in more symptomatic implant removal. Methods: We conducted a retrospective cohort study at our Level I trauma center. Seventy-five patients underwent surgical removal of symptomatic locking screws from 2007 to 2014 and were compared with a control group of 122 patients from the same time period who did not undergo symptomatic locking screw removal. Our main outcome measures were radiographic and demographic factors associated with implant removal. Results: Multivariable regression indicated that a proximal locking screw that started anterolateral and was directed posteromedial was the strongest radiographic predictor of symptomatic removal (odds ratio [OR], 2.83; p = 0.03). An Injury Severity Score <11 (OR, 3.10; p < 0.001) and a body mass index <25 kg/m 2 (OR, 2.15; p = 0.02) were also associated with locking screw removal. The final prediction model discriminated patients requiring symptomatic locking screw removal with moderate accuracy (area under the receiver operating characteristic curve = 0.73). Conclusions: The strongest radiographic predictor for symptomatic locking screw removal after tibial nail insertion was the direction of the most proximal locking screw. In contrast to previous research on retrograde femoral nails, tibial locking screws that were closer to the joints were not associated with an increased likelihood of symptomatic screw removal. Clinicians can use these data to help counsel patients regarding the likelihood of symptomatic screws and perhaps to help guide screw placement in cases with multiple options.